Effects of mobile phone usage behavior and mobile phone addiction among youth - Munusamy, Kalaivani; Ahmad Ghazali, Akmar Hayati (Human Resource Management Academic Research Society, 2020)
Mobile phone offers several benefits which ease community socializing and communication process. Moreover, mobile phone assists them in information and entertainment seeking process while at the same time act as safety tool during emergency situation. Nevertheless, albeit benefit offered, mobile phone has created problem to the community particularly to the young one whereby addiction is most obvious one. Such social issue however, seems to attract less internet from the scholars, which eventually lead to lack of understanding on this issue. Consequently, in addiction to this, the present research aims to investigate one of the significant areas of mobile phone usage to analyze the psychological context and the relationships for young users between mobile phone addiction and mobile phone usage. Based on this problems, this study was conducted to determine the level of mobile phone usage among youths; and to find out the level of the mobile phone addiction among youths. The research was carried out on 400 youths in Klang Valley using the survey method. The finding concludes that youths mobile phone usage behavior and addiction in moderate level. A serious attention must give to this issue before the youths addicted highly. All the responsible parties such as parents, educators and policy makers must work together to combat the negative impact of mobile phone addiction.